Seismic Assessment of Historical Masonry Buildings at Different Scale Levels: A Review - Irene Puncello; Silvia Caprili (Applied Sciences, 2023)
The relevant losses determined by recent earthquakes stressed the vulnerability of historical masonry constructions towards horizontal seismic actions, therefore highlighting the need for reliable approaches for the structural assessment and following retrofit. During the last decades, the scientific community has widely investigated the tools to analyse the performance of such structural typologies, resulting in a multitude of different methodologies depending on the building’s features and the goal of the analysis. The task is particularly challenging because of the frequently limited knowledge concerning the state of the art and the high structural complexity due to overlapped construction phases. A general literature review of the methods adopted for the structural assessment of historical masonry buildings is proposed in the present paper. The methods are grouped according to the operational scale, providing an overview of the current state of the art.